Convexification and Concavification for a General Class of Global Optimization Problems - Wu, Z. Y.; Bai, F. S.; Zhang, L. S. (Journal of global optimization, 2005)
A kind of general convexification and concavification methods is proposed for solving some classes of global optimization problems with certain monotone properties. It is shown that these minimization problems can be transformed into equivalent concave minimization problem or reverse convex programming problem or canonical DC programming problem by using the proposed convexification and concavification schemes. The existing algorithms then can be used to find the global solutions of the transformed problems. [PUBLICATION ABSTRACT]